Suppose that $L:K$ is a field extension, and $K_1, K_2$ are intermediate fields such that $L =K(K_1, K_2)$, then $[L:K]\leq [K_1:K][K_2:K]$. I prove it as follows:

Proof: Suppose $\{a_1,\ldots,a_n\}$ and $\{b_1,\ldots,b_m\}$ are bases for $K_1$ and $K_2$ respectively (over $K$). Now the set $\{a_ib_j : 1\leq i \leq n, 1\leq j \leq m \}$ spans $L$ (over $K$). Now said set has cardinality $nm = [K_1:K][K_2:K]$ and hence the inequality follows.

Is this proof correct or am I missing something? Some help will be much appreciated!

  • 1
    $\begingroup$ I think as a teacher I would like to see a proof for the claim that the $K$-span of the products $a_ib_j$ is a field, i.e. closed under products and inversions. Admittedly it is likely that useful lemmas have been covered earlier, and you can take advantage of those. $\endgroup$ – Jyrki Lahtonen Aug 25 '17 at 11:22
  • $\begingroup$ More specifically, if $[K_1:K]$ and $[K_2:K]$ are infinite, that claim about the span being a field is false. $\endgroup$ – Jyrki Lahtonen Aug 25 '17 at 11:23
  • $\begingroup$ @Jyrki Lahtonen Thank you! Can you give me a hint how one would have to prove the proposition in the infinite case? $\endgroup$ – Marcel S Aug 25 '17 at 11:27
  • $\begingroup$ For the purposes of this result the infinite case is kinda uninteresting for if either $[K_i:K]=\infty$ there is nothing to prove. My main point was that proving that $\{a_ib_j:i,j\}$ span $L$ in the case $[K_i:K]<\infty, i=1,2,$ requires you to justify that the span is a field. Otherwise you can't conclude that the span $=L$. $\endgroup$ – Jyrki Lahtonen Aug 25 '17 at 11:33

Based on @JyrkiLahtonen's comments above.

If either $[K_1 : K] = \infty$ or $[K_2 : K] = \infty$, then the inequality is trivially true. So, let both, $K_1/K$ as well as $K_2/K$ be finite extensions. Let $\{ a_1,\dots,a_n \}$ be a basis for $K_1$ over $K$ and let $\{ b_1,\dots,b_m \}$ be a basis for $K_2$ over $K$. Consider $V = \operatorname{span}_K\{ a_i b_j : 1 \leq i \leq n, 1 \leq j \leq m \}$, the vector subspace of $L$ spanned by the vectors $a_i b_j$ over the field $K$. We wish to show that $V$ is a field.

To show that $V$ is a ring, it suffices to show that $a_i b_j \cdot a_k b_l \in V$ for all $1 \leq i, k \leq n$, $1 \leq j, l \leq m$. Now, $$ a_i b_j \cdot a_k b_l = a_i a_k \cdot b_j b_l $$ and $a_i a_k \in K_1$, $b_j b_l \in K_2$. So, we can express them as a $K$-linear combinations of $ a_1,\dots,a_n$ and $b_1,\dots,b_m$, respectively. That is, $$ a_i a_k = \sum_{p = 1}^n c_{ikp} a_p \quad \text{and} \quad b_j b_l = \sum_{q = 1}^m d_{jlq} b_q $$ for some scalars $c_{ikp}, d_{jlq} \in K$. Hence, $$ a_i b_j \cdot a_k b_l = \left( \sum_{p = 1}^n c_{ikp} a_p \right) \cdot \left( \sum_{q = 1}^m d_{jlq} b_q \right) = \sum_{p=1}^n \sum_{q=1}^m (c_{ikp}d_{jlq}) a_p b_q \in V. $$ Hence, $V$ is a ring. In particular, $V$ is an integral domain because it is contained in $L$ which is a field.

Next, we need to show that the multiplicative inverse in $L$ of every non-zero element in $V$ lies in $V$ itself. Let $r \in V$, $r \neq 0$. Since $V$ is spanned over $K$ by a finite set, $V$ is a finite-dimensional vector space over $F$. If $\dim_K V = d$, then the set $\{ 1, r, r^2, \dots, r^d \}$ is a $K$-linearly dependent set. Hence, there exist $c_0,c_1,\dots,c_d \in K$, not all zero, such that $$ c_0 + c_1 r + c_2 r^2 + \dots + c_d r^d = 0. $$ Let $k = \min\{ 0 \leq i \leq d : c_i \neq 0 \}$. Then, $$ c_k r^k + c_{k+1} r^{k+1} + \dots + c_d r^d = 0.\tag{1} $$ It cannot be that $c_i = 0$ for all $i \neq k$ because otherwise we would have $$ c_k r^k = 0 \implies r^k = 0 \implies r = 0, $$ which is a contradiction. Note that here we are crucially using the fact that $V$ is an integral domain. So, we have concluded that $k < d$. Now, from $(1)$ we get that $$ \begin{align} & &c_k r^k + c_{k+1}r^{k+1} + \dots + c_d r^d &= 0 \\ &\implies &r^k(c_k + c_{k+1}r + \dots + c_d r^{d-k}) &= 0 \\ &\implies &c_k + c_{k+1}r + \dots + c_d r^{d-k} &= 0\\ &\implies &r(c_{k+1} + c_{k+2} r + \dots + c_d r^{d-k-1}) &= -c_k\\ &\implies &-c_k^{-1}(c_{k+1} + c_{k+2} r + \dots + c_d r^{d-k-1}) &= r^{-1}. \end{align} $$ So, $r^{-1}$ lies in the $K$-span of $\{ 1 , r, r^2, \dots, r^d \}$ which is a subspace of $V$. Therefore, $r^{-1} \in V$ for all nonzero $r \in V$. Thus, $V$ is a field.

Any field containing both $K_1$ and $K_2$ must contain $a_i b_j$ for all $1 \leq i \leq n$, $1 \leq j \leq m$. Hence, it must also contain the $K$-span of $\{ a_i b_j \}$. But we have just shown that this is a field, so it must be the minimal field containing both $K_1$ and $K_2$. In other words, $L = K(K_1,K_2) = V$. Thus, any basis for $L$ over $K$ can contain no more than $nm$ elements. In other words, $$ [L : K] \leq [K_1 : K] [K_2 : K]. $$ Hence, proved.


This is not an answer to the question, but instead expands on another comment of @JyrkiLahtonen, just to shed more light on the proof.

In proving that $V = \operatorname{span}_K\{ a_i b_j : 1 \leq i \leq n, 1 \leq j \leq m \}$ is a field, we crucially use the fact that it is a finite-dimensional vector space over $K$. To see why this is important, let $K = \mathbb{Q}$ and $L = \mathbb{Q}(x,y)$. Then, taking $K_1 = \mathbb{Q}(x)$ and $K_2 = \mathbb{Q}(y)$, we see that $L = K(K_1,K_2)$. Let $$ \mathcal{B}_1 = \left\{ \frac{f_i(x)}{g_i(x)} : i \in I \right\} $$ be a basis for $\mathbb{Q}(x)$ over $\mathbb{Q}$, and let $$ \mathcal{B}_2 = \left\{ \frac{h_j(y)}{k_j(y)} : j \in J \right\} $$ be a basis for $\mathbb{Q}(y)$ over $\mathbb{Q}$. Consider $V$, the $\mathbb{Q}$-span of the set $$ \mathcal{B} = \left\{ \frac{f_i(x)h_j(y)}{g_i(x)k_j(y)} : i \in I, j \in J \right\} $$ in $\mathbb{Q}(x,y)$. We claim that $\frac{1}{x+y} \in \mathbb{Q}(x,y)$ does not lie in $V$, and so the element $x+y \in V$ does not have a multiplicative inverse in $V$.

Suppose, for the sake of contradiction, that $$ \frac{1}{x+y} = \sum_{\substack{i \in I\\ j \in J}} a_{ij} \frac{f_i(x) h_j(y)}{g_i(x) k_j(y)} $$ where $a_{ij} \in \mathbb{Q}$ and all but finitely many of them are zero. Then, by clearing out denominators, we can write $$ \frac{1}{x+y} = \frac{\sum c_{ij}\tilde{f}_i(x)\tilde{h}_j(y)}{\prod d_{ij}\tilde{g}_i(x)\tilde{k}_j(y)}, $$ for some polynomials $\tilde{f}_i,\tilde{g}_i \in \mathbb{Q}[x]$ and $\tilde{h}_j, \tilde{k}_j \in \mathbb{Q}(y)$, $c_{ij}, d_{ij} \in \mathbb{Q}$, and where the sum and product are both finite.

Now, since $x+y$ is an irreducible polynomial in $\mathbb{Q}(x,y)$, it must divide the product in the denominator in the RHS. Since $\mathbb{Q}(x,y)$ is a UFD, we can write the denominator as a product of irreducibles. But $x+y$ cannot divide any of those irreducible factors because the factors are all polynomials purely in the variable $x$ or in the variable $y$. So, we have a contradiction.


Here is another way to solve the problem, using some basic results from field theory.

We assume that $K_1/K$ and $K_2/K$ are finite extensions, for otherwise the inequality is trivially true. Since $$ [L:K] = [L:K_1] \cdot [K_1:K], $$ it suffices to show that $$ [L:K_1] \leq [K_2 : K]. $$ Now, every finite extension is algebraic and finitely generated, so we can write $K_1 = K(a_1,\dots,a_n)$ and $K_2 = K(b_1,\dots,b_m)$, for some elements $a_1, \dots, a_n, b_1, \dots, b_m$ that are algebraic over $K$.

It is easy to see that $L = K(K_1,K_2) = K_1(b_1,\dots,b_m)$. Define $L_0 = K_1$ and $L_i = L_{i-1}(b_i)$ for each $1 \leq i \leq m$. So, we have a chain of simple extensions $$ K_1 = L_0 \subseteq L_1 \subseteq L_2 \subseteq \dots \subseteq L_m = L. $$ Similarly, define $F_0 = K$ and $F_i = F_{i-1}(b_i)$ for each $1 \leq i \leq m$. So, we have a chain of simple extensions $$ K = F_0 \subseteq F_1 \subseteq F_2 \subseteq \dots \subseteq F_m = K_2. $$ Since the extensions are simple (and algebraic), we have that $$ [L_i:L_{i-1}] = [L_{i-1}(b_i):L_{i-1}] = \deg \min(L_{i-1},b_i),\\ [F_i:F_{i-1}] = [F_{i-1}(b_i):F_{i-1}] = \deg \min(F_{i-1},b_i). $$ Note that $F_{i-1} \subseteq L_{i-1}$, so $\min(L_{i-1},b_i)$ divides $\min(F_{i-1},b_i)$, which implies that $\deg \min(L_{i-1},b_i) \leq \deg \min(F_{i-1},b_i)$. Therefore, $$ [L_i : L_{i-1}] \leq [F_i : F_{i-1}] $$ for each $1 \leq i \leq m$. Hence, $$ [L_m:L_0] = \prod_{i=1}^m [L_i : L_{i-1}] \leq \prod_{i-1}^m [F_i : F_{i-1}] = [F_m : F_0]. $$ In other words, $$ [L:K_1] \leq [K_2 : K]. $$ Hence, proved.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.